Editor's Note to Volume 4 of the Journal of Communication Pedagogy "If you build it, they will come." - Deanna D. Sellnow (Central States Communication Association, 2021)
This volume features instructional communication research articles ranging using mHealth patients with invisible chronic illnesses to machine teachers (e.g., Robots) as teachers. It also includes reflective and best practice essays on incorporating audio podcasts into teaching and learning, communication training and development in the multigenerational workforce, managing speech anxiety online, and the role of edutainment in teaching public relations.